The diastolic inflow and longitudinal movement of the heart in the African full-term newborn infant - Beckerling, BJ; Prakaschandra, DR; Hadebe, NM; Ntsinjana, HN; Cilliers, AM (SA Heart Journal, 2025)
Introduction: Echocardiography is essential in the assessment of systolic and diastolic left ventricular (LV) function. The diastolic component of the cardiac cycle which is a crucial aspect of cardiac output has been less researched in the neonatal population. Aim: To determine normal echocardiographic references for diastolic inflow and longitudinal movement of both the left and right heart in healthy full-term Black African neonates. Methodology: A descriptive, bidirectional study design was undertaken. Healthy African (Black) full-term newborn infants who met inclusion criteria were recruited at the Chris Hani Baragwanath Academic Hospital. Left and right ventricular (RV) systolic and diastolic function were assessed using various echocardiographic M-mode, flow Doppler and tissue Doppler measurements. Statistical analysis was performed using Excel and Statistica version 13.1. Normal ranges were calculated using means ± standard deviations. Results: Two hundred and ninety-two neonates (142 males, 152 females; median gestational age 39 weeks, range 37–42 weeks) were included in the study. Most subjects (175/292;60%) were born by caesarean section. Median body surface area was 0.20 m2 (range 0.16–0.25 m2). Median weight was 3.12 kg (range, 2.5–4.43 kg). Median post-delivery age at echocardiography was 31 hours (range 12–216 hours). The following measurements (means ±SD) were documented: LVEF and LVFS were 73.56% (±8.93) and 40.34% (±7.91) respectively. Mitral valve (MV) peak E = 0.58 m/s (±0.113), MV peak A = 0.59 m/s (±0.123), MV peak E/A ratio = 1.01 (±0.21), MV E’ = 0.058m/s (±0.012), MV E/E’ ratio = 10.38 (±2.65), MV S’ = 0.052 m/s (±0.009) and LV Tei = 0.306 (±0.139). Measurements pertaining to the RV function were: TAPSE = 7.51 mm (±1.304), tricuspid valve (TV) peak E = 0.512 m/s (±0.126), TV peak A = 0.616 m/s (±0.127), TV E/A = 0.845 (±0.199), TV E’ = 0.079 m/s (±0.021), TV E/E’ ratio = 6.78 (±2.02), TV S’ = 0.071 m/s (±0.045) and RV Tei = 0.283 (±0.132). Conclusion: This large study established normal reference values for diastolic function and longitudinal systolic and diastolic movement of the heart in healthy full-term African neonates using echocardiography.